Analisis Anggaran Evaluasi Proyek Rehabilitasi Pembangunan Gor dibagian Tribun Penonton Utara dan Selatan Stadion Mini & VIP Gor Jl.William Iskandar Kab. Deli Serdang - Siburian, Dodi J. R.; sitorus, Annisa M; Lumban Gaol, Rista Y; Br. Simarmata, Santa M; Hidayat, Nasrullah (Jurnal Sains dan Teknologi, 2023)
Sports Building (GOR) can be interpreted as a building that is used as a center for sports activities to increase interest in achievement. The category of sports that carry out activities inside the building is indoor sports activities. The main focus is for the rehabilitation construction project budget for the construction of the North and South Spectator Stands, Mini Stadium and VIP Gor. In this development project, the time period and budget costs will be considered to ensure the success of the rehabilitation project for the construction of the North and South Spectator Stands for the Mini Stadium and VIP Gor. runs smoothly and on time. This research uses a descriptive qualitative method, where this research uses primary data which is studied based on interviews and observations in the development project. The rehabilitation research on the construction of the North and South Spectator Stands for the Mini Stadium and VIP Gor Medan shows how the development is in line with the objectives achieved.